2012
DOI: 10.1021/nn300694v
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of Aptamer Switch Probes and Photosensitizer on Gold Nanorods for Targeted Photothermal and Photodynamic Cancer Therapy

Abstract: An aptamer switch probe (ASP) linking chlorin e6 (Ce6), a photosensitizer molecule, to the surface of gold nanorods (AuNRs) was used to target cancer cells for photodynamic therapy (PDT) and photothermal therapy (PTT). In the presence of target cancer cells, the ASP changes conformation to drive Ce6 away from the gold surface, thereby producing singlet oxygen for PDT upon light irradiation. Since each AuNR is modified with many ASP/Ce6 molecules, the AuNR/ASP/Ce6 conjugate yields enhanced binding and therapeut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
281
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 344 publications
(283 citation statements)
references
References 38 publications
(95 reference statements)
2
281
0
Order By: Relevance
“…Thus, we hypothesized that the use of AuNRs allows us to apply near-infrared (NIR) laser to generate heat efficiently through nonradiative processes (13,30,31). AuNRs, due to their unique chemical, physical, and optical properties, have been used in drug delivery (32), bioimaging, and PPTT of cancer (33)(34)(35)(36). NIR light is a low energetic (safe) light that can deeply penetrate the tissues, which could potentially enhance the AuNRs' effects on cytoskeletal proteins and inhibit migration.…”
Section: Significancementioning
confidence: 99%
“…Thus, we hypothesized that the use of AuNRs allows us to apply near-infrared (NIR) laser to generate heat efficiently through nonradiative processes (13,30,31). AuNRs, due to their unique chemical, physical, and optical properties, have been used in drug delivery (32), bioimaging, and PPTT of cancer (33)(34)(35)(36). NIR light is a low energetic (safe) light that can deeply penetrate the tissues, which could potentially enhance the AuNRs' effects on cytoskeletal proteins and inhibit migration.…”
Section: Significancementioning
confidence: 99%
“…At an irradiation power density of 5 mW/cm 2 , the temperature of PheoA-HA/AuNPs solution reached a final temperature of approximately 52 o C. Several groups have previously reported that unlike Au nanorods, AuNPs do not usually generate high temperatures. 12 Our investigation showed that the non-aggregated AuNPs generated limited heat of up to 35 o C. However, the final formulation, which is a combination of AuNPs along with a PS and polymers, led to the aggregation of several AuNPs within a single hybrid nanoparticle. Therefore, PheoA-HA/AuNPs generated greater heat compared with the free AuNPs alone.…”
Section: Resultsmentioning
confidence: 71%
“…11 Previous studies have reported that illuminated AuNPs within tumors can interact with external lasers and produce enough localized heat to destroy the tumor with little damage to the surrounding healthy tissue. 12,13 In combination with pheophorbide-A (PheoA), AuNPs could serve as a multifunctional theranostic nano-agent for cancer treatments with the potential for use as an efficient PS delivery platform for PDT. 14 In this study, we report that AuNPs encapsulated by PheoA-conjugated hyaluronic acid (HA) may target the CD44 receptors of cells and produce promising therapeutic effects against lung cancer cells (A549).…”
Section: Introductionmentioning
confidence: 99%
“…Several research groups have developed activatable aptamer-based methods which can be triggered by cancer biomarkers [42], membrane proteins, extracellular proteases [43], or cellular environments (e.g., pH) [44] or by other external stimuli, including artificial molecular switches [45]. For example, combination of a photosensitizer and ASP results in a switchable aptamer system which offers a reliable and versatile approach to the molecular mediation of singlet oxygen generation [46].…”
Section: Molecular Engineering Of a Switchable Aptamermentioning
confidence: 99%